An Analysis of the Dynamics of Aggregate Consumption in the Turkish Economy (1987-2019) - Erden, Hatice (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
This thesis aims to investigate the long-run and short-run relationships between consumption expenditure and income from 1987 to 2019 in Turkey. We used the Dual Adjustment approach that models the dual co-movements of the different components of time series variables. Data is sourced from World Bank’s database of World Development Indicators. We found empirical evidence on the presence of common trend for consumption and income in Turkey. Additionally, we found a significant relation among the transitory components of income and consumption. Turkish data reveals evidence on singular adjustment and hence lends support to the Dynamic Keynesian Consumption Function.

ÖZ: Bu tez, 1987'den 2019'a kadar Türkiye'de tüketim harcamaları ile gelir arasındaki uzun ve kısa vadeli ilişkiyi incelemeyi amaçlamaktadır. Zaman serisi değişkenlerinin farklı bileşenlerinin ikili ortak hareketlerini modelleyen İkili Uyarlanma yaklaşımını kullandık. Veriler Dünya Bankası’nın veri tabanından alınmıştır. Türkiye'de tüketim ve gelir için ortak bir eğilimin varlığına dair ampirik kanıtlar bulduk. Ek olarak, gelir ve tüketimin geçici bileşenleri arasında anlamlı bir ilişki bulduk. Türkiye verileri tekil uyarlanma ile uyumlu kanıtlar ortaya koymakta ve bu nedenle Dinamik Keynesyen Tüketim Fonksiyonunu desteklemektedir.
Master of Science in Economics. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2022. Supervisor: Prof. Dr. Mustafa İsmihan.
Keywords: Consumption (Economics)--Nigeria; Income; Household Consumption Expenditure; Dual Adjustment; Cointegration; Turkey